Modelling and performance evaluation of a pseudo-random impulse sequence for in situ parameter estimation in energy applications - Mwaniki, Frederick Mukundi (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.